Analysis of Metal Elements Contained in Graphite Target Coated With Chinese Medicinal Material Nanoparticles Using LIBS - Han, Weiwei; Wang, Yongqiang; Yin, Yaopeng; Li, Xuerui; Sun, Duixiong; Su, Maogen (Frontiers in Physics, 2022)
A nanoparticle-coated graphite target (NCGT) is presented to improve the analysis accuracy and stability of laser-induced breakdown spectroscopy (LIBS). A stable, relatively homogeneous, and close to optically thin laser-induced breakdown plasma was obtained by dispersing sample nanoparticles on a high-purity graphite substrate. Spectral structures dominated by the characteristic lines of carbon and the samples can greatly simplify spectral identification and avoid line interference. To maximize the analysis accuracy and stability, a series of experimental conditions were optimized step by step according to the spectral intensity and signal-to-noise ratio of the lines. Based on the final optimized conditions, the relative standard deviation values of Mg, Fe, and Sr elemental content in Chinese medicinal material (CMM) samples were reduced from 17.7, 16.6, 12.1% of the pressed target to 4.8, 9.5, and 4.5% of the NCGT, respectively. Comparisons with the inductively coupled plasma mass spectrometry (ICP-MS) results demonstrated that the present method has great potential for detection of LIBS.